Implementasi Diplomasi Indonesia Dalam Perang Dagang Terhadap Uni Eropa - Melda Alani Sitompul; Ibnu Zulian (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This article discusses the implementation of Indonesian diplomacy in facing the trade war against the European Union (EU) using a self-help concept approach. By analyzing the concept of self-help in international relations and its application in diplomatic strategy, this research highlights how Indonesia applies cooperative diplomacy with regional partners and diplomacy to overcome the challenges posed by the European Union's palm oil discrimination.This study uses a qualitative approach by collecting data from various primary sources of diplomatic documents related to the trade war involving the European Union. Apart from that, secondary data obtained from news, scientific articles and journals are relevant data sources.